FACTORS INFLUENCING HIV KNOWLEDGE AMONG WOMEN OF CHILDBEARING AGE IN SOUTH SUMATRA, INDONESIA - Najmah; Indah Purnama Sari; Tri Novia Kumalasari; Sharyn Graham Davies; Sari Andajani (Malaysian Journal of Public Health Medicine, 2020)
This study aims to provide detailed information on the role of the following social determinants (i.e. education, occupation, place of residence, marital and economic status) in the acquisition of HIV knowledge among women of childbearing age (15-49 years old). The study uses secondary data from the 2012 Indonesian Demographic and Health Survey (IDHS). The IDHS used a quantitative analytical approach with a cross-sectional study design and multi-stage stratified sampling. The sample included 1,335 women aged 15 to 49 years old living in South Sumatra Province, Indonesia. Descriptive analysis, ANOVA, and t-test and multiple logistic regressions were performed in this study. The results show one out of two women have little HIV knowledge. The more highly educated women were positively associated with a greater degree of knowledge related to comprehensive knowledge related to HIV (AOR: 3.7, 2.2-6.2, p.<0.05), HIV prevention (AOR:16.6, 1.8-153.9, p <0.05), transmission from mother to child (AOR:11.1, 3.3-36.9, p <0.05), HIV misconceptions (AOR:5.1, 1.1-23.1, p <0.05) and HIV services (AOR:5.7, 2.8-11.4, p < 0.05). In addition, the women lived in urban areas had more knowledge related to HIV prevention and transmission (AOR: 3.36, 1.8-6.2, p <0.05), and knowledge about mother-to-child of HIV transmission (AOR: 3.2, 1.8-5.5, p <0.05) compared to those who lived in rural areas. To conclude, education level was found to be the dominant factor associated with knowledge of HIV across all categories of knowledge after controlling by other determinants, age, marital status, working status and residence. HIV awareness and comprehensive HIV information among women who are considered to be in a low-risk group for HIV infection should be integrated with formal education as well as in maternal health services, particularly in rural areas.